Role of Low‐Density Lipoprotein in Early Vascular Aging Associated With Systemic Lupus Erythematosus. Issue 6 (30th April 2020) - Chan, Hua‐Chen; Chan, Hsiu‐Chuan; Liang, Chan‐Jung; Lee, Hsiang‐Chun; Su, Hung; Lee, An‐Sheng; Shiea, Jentaie; Tsai, Wen‐Chan; Ou, Tsan‐Teng; Wu, Cheng‐Chin; Chu, Chih‐Sheng; Dixon, Richard A.; et al.
Abstract : Objective: Patients with systemic lupus erythematosus (SLE) often have atherosclerotic complications at a young age but normal low‐density lipoprotein (LDL) levels. This study was undertaken to investigate the role of LDL composition in promoting early vascular aging in SLE patients. Methods: Plasma LDL from 45 SLE patients (SLE‐LDL) and from 37 normal healthy controls (N‐LDL) was chromatographically divided into 5 subfractions (L1–L5), and the subfraction composition was analyzed. Correlations between subfraction levels and signs of early vascular aging were assessed. Mechanisms of lipid‐mediated endothelial dysfunction were explored using in vitro assays and experiments in apoE −/− mice. Results: The L5 percentage was increased 3.4 times in the plasma of SLE patients compared with normal controls. This increased percentage of SLE‐L5 was positively correlated with the mean blood pressure (r = 0.27, P = 0.04), carotid intima‐media thickness (IMT) (right carotid IMT, r = 0.4, P = 0.004; left carotid IMT, r = 0.36, P = 0.01), pulse wave velocity (r = 0.29, P = 0.04), and blood levels of CD16+ monocytes (r = 0.35, P = 0.004) and CX3CL1 cytokines (r = 0.43, P < 0.001) in SLE patients. Matrix‐assisted laser desorption ionization–time‐of‐flight mass spectrometry analysis revealed that plasma levels of lysophosphatidylcholine (LPC) and platelet‐activating factor (PAF) were increased in SLE‐LDL and in the SLE‐L5 plasma subfraction. Injecting SLE‐LDL, SLE‐L5, or LPC into young, male apoE −/− mice caused increases in plasma CX3CL1 levels, aortic fatty‐streak areas, aortic vascular aging, and macrophage infiltration into the aortic wall, whereas injection of N‐LDL or SLE‐L1 had negligible effects (n = 3–8 mice per group). In vitro, SLE‐L5 lipid extracts induced increases in CX3CR1 and CD16 expression in human monocytes; synthetic PAF and LPC had similar effects. Furthermore, lipid extracts of SLE‐LDL and SLE‐L5 induced the expression of CX3CL1 and enhanced monocyte–endothelial cell adhesion in assays with bovine aortic endothelial cells. Conclusion: An increase in plasma L5 levels, not total LDL concentration, may promote early vascular aging in SLE patients, leading to premature atherosclerosis.